Analysis of soft rot Pectobacteriaceae population diversity in US potato growing regions between 2015 and 2022 - Ma, Xing; Zhang, Xiuyan; Stodghill, Paul; Rioux, Renee; Shrestha, Smita; Babler, Brooke; Rivedal, Hannah; Frost, Kenneth; Hao, Jianjun; Secor, Gary; Swingle, Bryan (Frontiers in Microbiology, 2024)
Soft rot Pectobacteriaceae (SRP) bacteria are globally dispersed pathogens that cause significant economic loss in potato and other crops. Our understanding of the SRP species diversity has expanded in recent years due to advances and adoption of whole-genome sequence technologies. There are currently 34 recognized SRP species that belong to the Dickeya and Pectobacterium genera. We used wholegenome sequencing based analysis to describe the current distribution and epidemiology of SRP isolated from diseased potato samples obtained from commercial potato cropping systems in the United States.Our primary objectives in the present study were to: 1) identify the species of these SRP isolates recovered from potato samples across 14 states in the US, 2) describe the variation among SRP isolates from various US locations and track their temporal changes, and 3) evaluate the evolutionary relationships among these SRP isolates to deduce their source. We collected 118 SRP strains from diseased potato plants and tubers in 14 states between 2015 and 2022. We identified three Dickeya and eight Pectobacterium species from diseased potato samples. Dickeya dianthicola, Pectobacterium parmentieri, P. carotovorum, and P. versatile appeared to be the predominant species, constituting 83% of the isolates. Furthermore, all D. dianthicola strains studied here as well as 90% of US D. dianthicola isolates sequenced to date exhibit significant clonality. The prevalence of this specific group of D. dianthicola, temporally and geographically, aligns with the occurrence of blackleg and soft rot outbreaks in the northeastern US after 2014. The genomic diversity observed in P. parmentieri implies multiple introductions to the US from at least four distinct sources, earlier than the arrival of the predominant group of D. dianthicola. In contrast, P. carotovorum and P. versatile appear to be widespread, long-term endemic strains in the US.